PENGARUH PENDIDIKAN KESEHATAN TEKNIK MENYUSUI PADA IBU POSTPARTUM SECTIO CAESAREA DI RUMKIT BHAKTI WIRA TAMTAMA SEMARANG: THE EFFECT OF HEALTH EDUCATION ON BREASTCHING ENGINEERING ON POSTPARTUM SECTION CAESAREA MOTHERS IN RUMKIT BHAKTI WIRA TAMTAMA SEMARANG - Yuni Astuti M.Kep; Tuti Anggarawati; Arifa Nur Khasanah; Dwi Riyanti (JURNAL KEPERAWATAN SISTHANA, 2020)
Breastfeeding is an activity that can bring happiness to mothers. Breastfeeding benefits by helping the mother from the delivery process, making the uterus contract quickly and prevent bleeding. Postpartum often have problems in the process of breastfeeding, especially mothers with caesarean section. Post SC delay in breastfeeding is caused by a lack of knowledge about how to breastfeed because the mother does not have adequate knowledge, the mother does not understand how to breastfeed properly, the benefits of breastfeeding and also the impact if the mother does not breastfeed her baby. One of the efforts to increase knowledge about breastfeeding is by providing health education. Giving information to post partum SC is very important in the success of mothers in providing exclusive breastfeeding. The purpose of knowing the effect of health education on breastfeeding techniques is correct in post partum SC. The research design will be conducted using pre-experimental (One group pre-posttest design) and sample selection using purposive sampling. The results of the influence of health education on breastfeeding techniques to increase knowledge of postpartum SC mothers with a p value of 0.001